Some results on value distribution concerning Hayman's alternative - Zhuang Xinyu; Zheng Ruilin; He Zhiying; Fang Mingliang (Open Mathematics)
In this article, we study the value distribution of meromorphic functions concerning Hayman’s alternative. We extend and improve some results due to Zhu [A far-reaching form of Hayman’s inequality; fixed points of meromorphic functions and their derivatives, Kexue Tongbao (Chinese) 31 (1986), no. 11, 801–804], Hua and Chuang [On a conjecture of Hayman, Acta Math. Sinica (N.S.) 7 (1991), no. 2, 119–126], and Charak and Singh [A value distribution result related to Hayman’s alternative, Commun. Korean Math. Soc. 34 (2019), no. 2, 495–506].